Can we persuade company car drivers to opt out? - De Wilde, Liesbeth; Stas, Lara; Savieri, Perseverence; Vanhaverbeke, Lieselot; Keserü, Imre; Macharis, Cathy (Frontiers in Sustainability, 2023)
Multiple issues are associated with company cars in the academic debate, such as excessive car use and welfare loss. Company cars, provided by organizations to their employees, are often seen as a subsidy for private car ownership throughout Europe, but especially in Belgium. Belgium is the first country in Europe to develop a legal framework in which organizations can replace the company car system with alternative solutions such as a corporate mobility budget. The objective of this study is to gain insight into the intentions of employees to replace their company car with this mobility budget. We have carried out an online survey among 527 company car drivers to predict the financial compensation that is required to replace the company car with more sustainable transport modes. On average, respondents required €683 per month to give up their company car. A stepwise linear regression analysis identified familiarity with alternative transport modes, environmental concern, accessibility and income as the primary predictors of this financial preference. These variables have been proven to be significant predictors of mode choice as well. The findings can help to identify opportunities for generating a modal shift in organizations.